Collaborative maintenance service and component sales under coopetition patterns for OEMs challenged by booming used-component sales. (October 2022) - Zhu, Ying; Xia, Tangbin; Hong, Ge; Chen, Zhen; Pan, Ershun; Xi, Lifeng
Highlights: The collaborative optimization of maintenance service and component sales is investigated. Three coopetition patterns for OEMs to deal with new challenges are characterized. The application of used components is integrated into preventive replacement policy. The decisions on sales price and acquisition ability for used components are jointly considered. The findings help OEMs determine the most profitable way in different market environments. Abstract: Nowadays, in the maintenance, repair, and overhaul (MRO) market of capital-intensive equipment, the booming used-component sales pose challenges for original equipment manufacturers (OEMs) in both maintenance services and component sales. To deal with these new challenges, this paper investigates the optimal maintenance service and component sales strategy for OEMs. Considering that the application of used components enhances the advantages of independent maintenance providers (IMPs), the preventive replacement policy utilizing used components is introduced into the maintenance service strategy. Meanwhile, for the threat to the sales of OEM components caused by used-component suppliers (UCSs), the sales price and acquisition ability decisions are jointly considered in the used-component sales strategy. By capturing their impacts on customer utility, the competition in maintenance services and used-component sales are analyzed. Then, by characterizing various coopetition relationships, we propose the optimization models under three patterns of used-component sales: independent operation, cooperation with UCS, and cooperation with IMP. With these models, an OEM can determine the collaborative optimization strategy to obtain the most profitable way under each pattern. Furthermore, through the sensitivity analysis, we provide OEMs with important managerial insights into the pattern selection in different market environments.